Power density of rectangular microstrip patch antenna arrays for 5G indoor base station - Nor Adibah Ibrahim; Tharek Abd Rahman; Razali Ngah; Omar Abd Aziz; Olakunle Elijah (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The fifth-generation (5G) network has been broadly investigated by many researchers. The capabilities of 5G include massive system capacity, incredibly high data rates everywhere, very low latency and the most important point is that it is exceptionally low device cost and low energy consumption. A key technology of 5G is the millimeter wave operating at 28 GHz and 38 GHz frequency bands which enable massive MIMO and small cell base station densification. However, there has been public concern associated with human exposure to electromagnetic fields (EMF) from 5G communication devices. Hence, this paper studies the power density of a 5G antenna array that can be used for the indoor base station. The power density is the amount of power or signal strength absorbed by a receiver such as the human body located a distance from the base station. To achieve this, the design of array antennas using CST software at 28 GHz, fabrication and measurement were carried out in an indoor and hallway environment. The measurement processes were set up at IC5G at UTM Kuala Lumpur in which the distance of the transmitter to receiver where 1 m, 4 m, 8 m, and 10 m. In this study, the measured power density is found to be below the set limit by ICNIRP and hence no health implication is feared. Regardless, sufficient act of cautionary has to be applied by those staying close to small cell base stations and more studies are still needed to ensure the safety of use of 5G base stations.